2013
DOI: 10.1159/000350866
|View full text |Cite
|
Sign up to set email alerts
|

DMSO-Soluble Cigarette Smoke Particles Alter the Expression of Endothelin B Receptor in Rat Coronary Artery

Abstract: In coronary artery diseases, cigarette smoking is a risk factor and the endothelin system plays a key role in the pathogenesis. This study was to examine if dimethylsulfoxide-soluble smoke particles (DSP) upregulate endothelin type-B (ETB) receptors in the coronary artery and investigate the mechanism. The isolated rat coronary arteries were organ-cultured for 24 h. The contractile response of the coronary artery was recorded by myograph. The mRNA and protein expression of the ETB recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…It has been suggested that MAPK (Huang et al, 2013;Uddman et al, 2003;Xu et al, 2008) signaling pathway is involved in the transcriptional upregulation of ET B receptor. The present study demonstrated that treatment with CsA increased phosphorylation of ERK1/2 and p38.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that MAPK (Huang et al, 2013;Uddman et al, 2003;Xu et al, 2008) signaling pathway is involved in the transcriptional upregulation of ET B receptor. The present study demonstrated that treatment with CsA increased phosphorylation of ERK1/2 and p38.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory NF-kB signaling pathway is also involved in the transcriptional upregulation of ET B receptor (Huang et al, 2013;Xu et al, 2008;Zheng et al, 2010). Moreover, it has been reported that activation of NF-kB was depended on both ERK1/2 and p38 MAPK signaling pathways (Chen et al, 2004;Kim et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arterial segments were given an initial tension of 1.2 mN and were left alone to adjust to this tension for 1 h. The contractile capacity of the artery was determined by exposure to a potassium-rich (63.5 m M ) Krebs solution that had the same composition as the previous solution except that NaCl was exchanged for KCl [26]. The potassium-induced contraction was used as a reference for the contractile capacity of the artery, and segments were used only if the potassium-elicited reproducible responses were >1.0 mN [27,28].…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have demonstrated that MAPK pathways have been shown to be associated with the GPCRs upregulation in human and rat vasculatures . In addition, over expression of contractile GPCRs in arteries were observed in rats exposed to cigarette smoke in vitro and vivo . Analytical research has demonstrated that cigarette smoke contains lots of PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%